THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AND WORK COMPETENCY AS A MEDIATING VARIABLE AT PT. BPRS AL SALAAM AMAL SALMAN, DEPOK CITY, WEST JAVA - Nuraeni Nuraeni; Gofur Ahmad; Moh. Matin; Suhendar Sulaiman; Fadhilah Izhari (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2022)
The purpose of this study is to determine: (1) The Effect of Work Motivation on Work Competence, (2) The Effect of Work Discipline on Work Competence, (3) The Effect of Work Motivation on Employee Performance, (4) The Effect of Work Discipline on Employee Performance, (5) Effect of Work Competence on Employee Performance, (6) Effect of Work Motivation on Employee Performance Mediated by Work Competency Variables, (7) Effect of Work Discipline on Employee Performance Mediated by Work Competency Variables. The data analysis model used is path analysis with associative quantitative research methods, with a population of 311 and a sample of 172. The study results indicate that this means that: (1) Work motivation has no significant effect on work competence. (2) Work Discipline has a significant effect on work competence. (3) Work motivation has no significant effect on performance. (4) Work discipline has no significant effect on performance. (5) Work competence has a significant effect on performance. (6) Work motivation on performance through work competence has an indirect effect. (7) Work discipline on performance through work competence has a direct effect.